A composite solid electrolyte, a solid-state battery

CN122950581APending Publication Date: 2026-10-20TIANMU LAKE INST OF ADVANCED ENERGY STORAGE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611266158.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]然而,复合固态电解质仍然存在多方面技术制约

Benefits of technology

[0017]与现有技术相比,本发明选择可聚合离子液体单体和卤化物固态电解质作为确保本征离子电导率和刚柔兼顾的基础体系,通过协同引入具有苯基硼酸频哪醇酯基的化合物与可聚合离子液体单体和卤化物固态电解质之间形成多重吸附和共轭关系,消除体系中多因素交互可能带来的界面副反应加剧,在确保离子传输效率的同时提升界面接触稳定性,离子电导率能够突破至4 mS/cm以上,对Li负极界面能够在高压(4.2V)高倍率(1C)循环条件下长期稳定,200圈循环容量保持率不低于80%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention provides a composite solid electrolyte, comprising polymerizable ionic liquid monomers, crosslinking agents, additives, initiators, diluents, alkali metal salts, and halide solid electrolytes. The additives are selected from at least one compound having a pinacol ester group of phenylboronic acid. The synergistic optimization of material selection in this invention ensures excellent mechanical flexibility and film-forming processability of the electrolyte membrane while successfully achieving high ionic conductivity, good mechanical properties, and long cycle life, meeting the practical application requirements of high-rate fast-charging solid-state batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery material technology, specifically relating to a composite solid electrolyte and its battery. Background Technology

[0002] All-solid-state batteries, which use non-flammable solid electrolytes instead of traditional flammable liquid electrolytes, offer improved safety and the potential to achieve higher energy densities, making them a core development direction for next-generation energy storage technologies. Optimizing the performance of solid-state electrolytes is crucial for the commercialization of all-solid-state batteries. Single-component solid electrolytes, such as polymers, oxides, sulfides, and halides, are limited by their intrinsic material properties, making it difficult to simultaneously meet multiple requirements such as high ionic conductivity, a wide electrochemical window, mechanical strength, and interfacial compatibility. For example, while polymer electrolytes are flexible and easy to process, they have low room-temperature ionic conductivity; oxide electrolytes have high chemical stability but poor interfacial impedance; and sulfide electrolytes have the highest ionic conductivity but are sensitive to air. This has prompted researchers to explore composite strategies that leverage the strengths of each component while mitigating their weaknesses.

[0003] Composite solid electrolyte technology primarily aims to achieve comprehensive optimization of electrical performance through the combination of different solid electrolyte components, typically by introducing inorganic fillers into a polymer electrolyte matrix. In terms of material selection, inert fillers such as Al₂O₃ can improve conductivity by reducing polymer crystallinity; active fillers such as oxide, sulfide, and halide solid electrolytes utilize their own ion channels to construct a fast ion network. Regarding structural design, a three-dimensional continuous framework, such as an electrospun LLZO framework, combined with polymer infiltration, forms a high-strength, high-conductivity structure. In terms of processing, surface-initiated in-situ polymerization coating and chemical anchoring form a controllable coating layer, improving the dispersibility and interfacial compatibility of inorganic fillers in the polymer matrix. The above solutions can be optimized according to the target performance combination, synergistically improving ionic conductivity, mechanical strength, and interfacial stability.

[0004] However, composite solid electrolytes still face several technical constraints. First, it is often difficult to achieve both ionic conductivity and mechanical properties in composite strategies. When the inorganic filler content is low, the ionic conductivity is generally below 1 mS / cm, which is insufficient to meet the requirements of room temperature fast charging. While increasing the inorganic filler content can improve conductivity, it can compromise the flexibility of the polymer matrix, leading to increased brittleness and difficulty in film formation of the composite solid electrolyte membrane. Second, the organic-inorganic interface has poor compatibility. Inorganic fillers are prone to agglomeration in the polymer matrix, and uneven dispersion can block ion conduction pathways. At the same time, the high interfacial impedance between different materials means that interfacial side reactions and mechanical exfoliation during long-term cycling can accelerate performance degradation, and the interfacial stability remains unsatisfactory.

[0005] Therefore, how to overcome the bottleneck of ionic conductivity while maintaining good processability and flexibility, and at the same time significantly improve interfacial compatibility and suppress performance degradation during cycling, so as to achieve long-term cycle stability under high-rate fast charging, is a technical problem that urgently needs to be solved in this field, and is also the key to promoting the practical application of high-energy-density solid-state batteries. Summary of the Invention

[0006] This invention addresses the aforementioned problems in the prior art by providing a novel composite solid electrolyte solution. Through the synergistic optimization of polymerizable monomers, additives, and specific inorganic fillers, it not only ensures the excellent mechanical flexibility and film-forming processability of the electrolyte membrane, but also effectively inhibits the aggregation of inorganic fillers while achieving high loading, significantly reducing the organic-inorganic interface impedance. Furthermore, it synergistically improves ion transport efficiency and interfacial contact stability, thus successfully balancing high ionic conductivity, good mechanical properties, and long cycle life, meeting the practical application requirements of high-rate fast-charging solid-state batteries.

[0007] To achieve the above objectives, the main technical solution adopted by the present invention is as follows:

[0008] A composite solid electrolyte, the raw materials of which include polymerizable ionic liquid monomers, crosslinking agents, additives, initiators, diluents, alkali metal salts and halide solid electrolytes;

[0009] The additive is selected from at least one of compounds having a phenylboronic acid pinacol ester group.

[0010] In some schemes,

[0011] The mass ratio of the polymerizable ionic liquid monomer to the crosslinking agent is (5~20):1;

[0012] The additive is present in an amount of 5 wt% to 20 wt% of the total mass of the polymerizable ionic liquid monomer and crosslinking agent.

[0013] The initiator is present in an amount of 0.5 wt% to 5 wt% of the total mass of the polymerizable ionic liquid monomer and the crosslinking agent.

[0014] The mass ratio of the diluent to the total mass of the polymerizable ionic liquid monomer and the crosslinking agent is (1~5):1;

[0015] The molar concentration of the alkali metal salt relative to the total mass of the polymerizable ionic liquid monomer, crosslinking agent, and diluent is 0.5 mol / kg to 2 mol / kg.

[0016] The mass of the halide solid electrolyte is 10 wt% to 50 wt% of the total mass of the polymerizable ionic liquid monomer, crosslinking agent and diluent.

[0017] Compared with existing technologies, this invention selects polymerizable ionic liquid monomers and halide solid electrolytes as the basic system to ensure intrinsic ionic conductivity and a balance between rigidity and flexibility. By synergistically introducing compounds with phenylboronic acid pinacol ester groups, multiple adsorption and conjugation relationships are formed between the polymerizable ionic liquid monomers and halide solid electrolytes, eliminating the exacerbation of interfacial side reactions that may be caused by the interaction of multiple factors in the system. While ensuring ion transport efficiency, the interfacial contact stability is improved, and the ionic conductivity can be broken through to above 4 mS / cm. The Li anode interface can be long-term stable under high voltage (4.2V) and high rate (1C) cycling conditions, and the capacity retention rate is not less than 80% after 200 cycles. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 This is a lithium-ion transference number test graph from Example 2 of the present invention.

[0020] Figure 2 This is a lithium-ion transference number test graph from Example 4 of the present invention.

[0021] Figure 3 This is a lithium-ion transference number test graph from Example 8 of the present invention.

[0022] Figure 4 This is a lithium-ion transference number test graph from Example 13 of the present invention.

[0023] Figure 5 This is a lithium-ion transference number test graph from Example 14 of the present invention.

[0024] Figure 6 This is a lithium-ion transference number test chart for Comparative Example 1 of the present invention. Detailed Implementation

[0025] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Furthermore, it should be understood that the specific embodiments described herein are only for illustration and explanation of the present invention and are not intended to limit the present invention.

[0026] Unless otherwise specified and in the absence of elemental conflicts, "halogen" in this invention includes F, Cl, Br, and I.

[0027] The composite solid electrolyte provided by this invention comprises polymerizable ionic liquid monomers, crosslinking agents, additives, initiators, diluents, alkali metal salts, and halide solid electrolytes as raw materials.

[0028] The additive is selected from at least one of compounds having a phenylboronic acid pinacol ester group.

[0029] The solid-solid contact mode, primarily using inorganic fillers in solid-state electrolytes, is one of the main factors limiting ionic conductivity. Selecting solid-state electrolyte materials with higher intrinsic conductivity is crucial to meeting the demands of high-rate fast charging applications. Halide and sulfide solid-state electrolytes have essentially the same conductivity order of magnitude, generally 1-2 orders of magnitude higher than oxide solid-state electrolytes. However, sulfide solid-state electrolytes are prone to oxidation and decomposition under voltages >2.5 V and are sensitive to air / moisture, easily releasing highly toxic H2S gas. Therefore, halide solid-state electrolytes are the preferred material system for overcoming the ionic conductivity bottleneck in this invention.

[0030] However, halide solid electrolytes still have limitations in their effectiveness. The high Young's modulus and hardness of halide solid electrolyte particles restrict their compaction and density, making it difficult to effectively improve the persistent problem of poor solid-solid contact, and thus failing to effectively enhance their interfacial compatibility with general polymer matrices. Furthermore, halide solid electrolytes are unstable to lithium, and usually require a protective layer to avoid direct contact with the lithium anode.

[0031] Polymerizable ionic liquid monomers are a class of molten salt compounds composed of anions and cations, exhibiting excellent flexibility. This invention utilizes polymerizable ionic liquid monomers instead of conventional polymerizable monomers, representing the optimal choice for effectively improving contact issues with halide solid electrolytes. A polymer matrix is ​​formed by the polymerization of polymerizable ionic liquid monomers and crosslinking agents, with the halide solid electrolyte dispersed and filled within the polymer matrix. This results in a composite solid electrolyte possessing both excellent flexibility and processability, as well as the rigidity of a dispersed supporting framework. Furthermore, polymerizable ionic liquids offer unparalleled conductivity advantages compared to conventional polymerizable monomers, enabling the construction of a three-dimensional transport network with halide solid electrolytes exhibiting similarly high intrinsic conductivity.

[0032] However, the soft nature of polymerizable ionic liquids also presents them with the challenge of easy decomposition. Simultaneously, the relatively high catalytic activity of the metal centers in halide electrolytes further exacerbates the unstable decomposition of polymerizable ionic liquids at the interface. Furthermore, the anion-cation salt system of polymerizable ionic liquids exhibits more significant concentration polarization under high voltage, and the concentration of local charge and electric field further induces the reductive decomposition and dendrite deposition of halide electrolytes at the interface. The superposition of these multiple factors makes the interfacial stability problem between halide solid electrolytes and polymerizable ionic liquid monomers particularly prominent.

[0033] Compounds containing the pinacol ester group of phenylboronic acid have a benzene ring linked by CB and a dioxoboron five-membered ring. The two rings are nearly coplanar, the CB-linked segment can rotate slightly but the potential barrier is not high, the empty p orbital of B can be partially delocalized with the π system of the benzene ring, and the benzene ring slightly donates electrons to the p orbital of B to appropriately reduce the Lewis acidity of B. At the same time, the four methyl groups of pinacol provide β-position steric shielding for B. These structural features give compounds containing the pinacol ester group of phenylboronic acid a significant advantage in improving the interfacial stability between halide solid electrolytes and polymerizable ionic liquid monomers. On the one hand, the benzene ring and the four-methyl five-membered ring effectively modulate the electron-withdrawing ability of the empty p orbitals of B, giving it a suitable adsorption capacity for the lone pair electrons of organic anions in polymerizable ionic liquids, thus effectively restricting anion migration. On the other hand, the benzene ring and the four-methyl five-membered ring also provide suitable protection for B, which serves as the active center, eliminating concentration polarization. This allows B to effectively prevent dissociation induced by the metal center of the halide solid electrolyte while restricting anion migration. Furthermore, the ring structure of the benzene ring and the dioxoboron five-membered ring can also serve as a site center to promote ion migration and conduction, synergistically enhancing the ion conduction coordination of the three-dimensional transport network at the interface. Ultimately, compounds with phenylboronic acid pinacol ester groups can significantly improve the ion conduction capacity of the system while stabilizing the interface, effectively increasing the ion transference number and battery performance of the composite solid electrolyte.

[0034] The above-mentioned components of the present invention can be further adapted to a suitable ratio to optimize the synergistic effect and make the construction of the three-dimensional transmission network more uniform.

[0035] In some examples,

[0036] The mass ratio of the polymerizable ionic liquid monomer to the crosslinking agent is (5~20):1;

[0037] The additive is present in an amount of 5 wt% to 20 wt% of the total mass of the polymerizable ionic liquid monomer and crosslinking agent.

[0038] The initiator is present in an amount of 0.5 wt% to 5 wt% of the total mass of the polymerizable ionic liquid monomer and the crosslinking agent.

[0039] The mass ratio of the diluent to the total mass of the polymerizable ionic liquid monomer and the crosslinking agent is (1~5):1;

[0040] The molar concentration of the alkali metal salt relative to the total mass of the polymerizable ionic liquid monomer, crosslinking agent, and diluent is 0.5 mol / kg to 2 mol / kg.

[0041] The mass of the halide solid electrolyte is 10 wt% to 50 wt% of the total mass of the polymerizable ionic liquid monomer, crosslinking agent and diluent.

[0042] In some examples, the halide solid electrolyte has the general formula Li a M b X c Y d Where 1.5≤a≤3, 0.5≤b≤1.5, 3.5≤c≤6.5, 0≤d≤1.0; M is selected from at least one of Zr, Hf, Ti, Ta, Nb, Y, Sc, In, Al, Mg, Zn, and La; X is selected from at least one of Cl, Br, and I; Y is selected from at least one of O, S, and Se; and when d>0, the electrolyte is an oxyhalide solid electrolyte, a sulfur halide solid electrolyte, or a selenium halide solid electrolyte.

[0043] For example, including Li3InCl6, Li3YCl6, Li3La 0.8 Y 0.2 Cl6, Li 2.9 Al 0.1 InCl6, Li3InCl 5.8 Br 0.2 Li 1.75 ZrCl 4.75 O 0.5 Li2TiCl5O 0.3 Li2HfCl5O 0.3 Li 2.5 NbCl5O 0.75 One or more of the following.

[0044] In some examples, the structure of compound I having a pinacol ester group of phenylboronic acid is as follows:

[0045] , Formula I,

[0046] Where n = 0 or 1, n = 0 indicates that C and B on the benzene ring are directly connected;

[0047] R1, R2, and R3 are each independently selected from H, halogen, ether, hydroxyl, carboxyl, carbonyl, amino, cyano, isocyano, nitro, nitroso, acyloxy, amide, azide, formyl, carbamoyl, silyl, siloxy, mercapto, sulfonic acid, sulfonyl, sulfinyl, ester, C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, borate, phosphate, C3-C4 cycloalkyl, ternary or quaternary heterocyclic groups, and optionally further substituted by hydrogen, halogen, hydroxyl, cyano, amino, C1-C4 alkyl or C1-C4 alkoxy.

[0048] Furthermore, based on further systematic research, this invention provides a more optimized combination system by gaining a deeper understanding of the fine balance control of the nonlinear gain effect at the microscale of halide solid electrolytes, polymerizable ionic liquid monomers, and compounds with phenylboronic acid pinacol ester groups.

[0049] In some preferred examples,

[0050] The halide solid electrolyte is an oxyhalide solid electrolyte;

[0051] The polymerizable ionic liquid monomer is an ionic liquid monomer containing a heterocyclic cation center;

[0052] The compound having a phenylboronic acid pinacol ester group is the compound with n=0 in Formula I.

[0053] In halide solid electrolytes, the main components constituting the ion transport framework are halide anions X (Cl, Br, I). These halide anions are arranged in space to form cubic close-packed or hexagonal close-packed sublattices. High-valence metal elements M (such as Zr, Hf, Y, In, etc.) selectively occupy the octahedral voids formed by the above-mentioned close-packed anion sublattices, forming MX6 or M(O / Cl)6 octahedral structural units. These octahedra are connected by sharing vertices or edges, constructing a three-dimensional or two-dimensional extended rigid framework. Lithium ions (Li... + Lithium ions are distributed in the remaining interstitial sites of the close-packed anion sublattice, mainly involving octahedral interstitials (Oct) and tetrahedral interstitials (Tet). Under the action of an electric field, lithium ions migrate in the lattice through the Oct-Tet-Oct or intralayer octahedral hopping mechanism.

[0054] The preferred oxyhalide solid electrolyte, as a preferred branch of the present invention, brings local alternation or defects in the stacked sequence inside the material, which broadens the ion transport channels, but also brings the risk of further exposure of the further active metal element M.

[0055] The above-mentioned risks were further adapted and eliminated by using polymerizable ionic liquid monomers containing heterocyclic cation centers. The heterocyclic cation centers also bring large π bonds, which form π-π stacking with the benzene ring of the phenylboronic acid pinacol ester group, further adsorbing the additive firmly onto the polymer chain, and weakening the influence of the active metal element M in the oxyhalide solid electrolyte on the polymer matrix through adsorption isolation.

[0056] Meanwhile, compounds with phenylboronic acid pinacol ester groups adopt a configuration in which C and B on the benzene ring are directly linked, which further balances the dual effects of the benzene ring feeding electrons to B to reduce acidity and protecting B from dissociation. It also indirectly regulates the electron cloud of the benzene ring through π-π stacking, so that the micro-control of the interface achieves the best effect on the compatibility of the oxygen halide solid electrolyte.

[0057] In some examples, the halide solid electrolyte is selected with a nanoscale particle size, preferably with a D50 of 5-300 nm, and more preferably with a D50 of 5-100 nm. Nanoscale particle size facilitates better skeletal support and ion conduction within the thin polymer matrix, ensuring film flexibility. Simultaneously, this invention benefits from the excellent π-π adsorption and dissociation protection capabilities of the additives and polymerizable ionic liquid monomers, enabling the use of halide solid electrolyte particles with a lower nanoscale particle size range to optimize the three-dimensional transport network, without exacerbating interfacial instability issues caused by increased exposure of metal elements (M) at smaller particle sizes.

[0058] In some further examples, the oxyhalide solid electrolyte uses M containing at least Zr and d satisfying 0.1≤d≤1.0.

[0059] Specifically, for example, oxygen halide solid electrolytes have the general formula Li a Zr b-α M' α Cl c O d , where 1.5≤a≤2, 0.9≤b≤1.1, 0≤α≤0.3, 3.5≤c≤5.5, 0.1≤d≤1.0; M' is selected from at least one of Hf, Ti, Ta, Nb, Y, Sc, In, Al, Mg, Zn, and La.

[0060] The above general formula represents a further branch of Zr-based oxychloride solid electrolytes. Structurally, it is a multiphase coexistence, highly amorphous powder system near the phase boundary. It has a significantly reduced lithium-ion migration activation energy barrier in halide solid electrolyte systems, further optimizing the unity of high ionic conductivity and excellent cold-pressing compaction. In this structure, the atomic sizes of Zr and Cl are more conducive to the stability of ZrCl6 octahedron. At the same time, Zr metal has lower dissolution and catalytic activity in the system, which is more advantageous in the system of this invention.

[0061] Substituents attached to a benzene ring can be classified into two categories based on their effect on the electron cloud density of the benzene ring: electron-donating functional groups and electron-withdrawing functional groups. Specifically, "electron-donating functional groups" refer to groups that increase the electron cloud density of the benzene ring relative to hydrogen; "electron-withdrawing functional groups" refer to groups that decrease the electron cloud density of the benzene ring relative to hydrogen. The specific classification of a group is generally based on its net inductive / conjugative effect when attached to the benzene ring.

[0062] For example, electron-donating functional groups include alkyl, cycloalkyl, phenyl, hydroxyl, alkoxy, acyloxy, amino, alkylamino, acylamino, mercapto, alkylthio, etc.

[0063] For example, electron-withdrawing functional groups include halogen, nitro, cyano, aldehyde, acyl, carboxyl, ester, amide, sulfonyl, trifluoromethyl, etc.

[0064] In some further examples, the present invention has found that in the compounds containing the phenylboronic acid pinacol ester group, when an electron-withdrawing functional group is attached to the benzene ring to appropriately reduce the electron cloud density of the benzene ring, a better system advantage is exhibited. This may be because the electron-withdrawing functional group appropriately weakens the degree to which the benzene ring provides electrons to the p orbitals of B, making B more conducive to enhancing the adsorption and fixation of organic anions, thereby increasing the lithium (sodium) ion transference number of the composite solid electrolyte.

[0065] When multiple substituents (R1, R2, R3) are present on the benzene ring, the sum of the inductive and conjugation effects of these substituents constitutes the net electron effect on the benzene ring. If the net electron effect increases the electron cloud density of the benzene ring relative to hydrogen, the benzene ring can be called an electron-donating modified benzene ring; if it decreases the electron cloud density, the benzene ring can be called an electron-withdrawing modified benzene ring. It is readily understood that, in the compounds of the present invention containing a pinacol ester group of phenylboronic acid, electron-withdrawing modification of the benzene ring is more preferred.

[0066] In some further examples, the structure of compound formula II having a pinacol ester group of phenylboronic acid is as follows:

[0067] Formula II

[0068] R4 is selected from an electron-withdrawing functional group whose main chain length does not exceed four atoms; preferably a strong electron-withdrawing functional group; specifically, it can be selected from one of nitro, cyano, trifluoromethyl, quaternary ammonium, aldehyde, acyl, carboxyl, ester, amide, sulfonic acid, sulfonyl and trialkyl halo.

[0069] As some specific examples, compounds having a phenylboronic acid pinacol group are selected from at least one of 4-acetoxyphenylboronic acid pinacol ester (a), 3-fluoro-4-cyanophenylboronic acid pinacol ester (b), 4-trimethsilylphenylboronic acid pinacol ester (c), phenylboronic acid pinacol ester (d), 3,5-bis(methoxycarbonyl)phenylboronic acid pinacol ester (e), 4-fluorobenzylboronic acid pinacol ester (f), 4-(cyanomethyl)phenylboronic acid pinacol ester (g), 2-(azidomethyl)phenylboronic acid pinacol ester (h); 4-methoxycarbonylphenylboronic acid pinacol ester (i); 2-fluoro-5-(methoxycarbonyl)phenylboronic acid pinacol ester (j); and 3-chloro-4-nitrophenylboronic acid pinacol ester (k).

[0070]

[0071] In some further examples, the polymerizable ionic liquid monomer includes at least one of a nitrogen-containing heterocyclic cation central group. Exemplarily, the nitrogen-containing heterocyclic cation central group is selected from imidazole-based cationic groups, pyridine-based cationic groups, pyrrole-based cationic groups, and piperidine-based cationic groups.

[0072] In some further examples, the polymerizable group of the polymerizable ionic liquid monomer is selected from at least one of vinyl, propenyl, allyl, and acryloyloxy groups.

[0073] In some further examples, the anionic group of the polymerizable ionic liquid monomer is selected from one of halide ions, phosphate ions, perchlorate ions, sulfonamide ions, oxalate-borate ions, sulfonate ions, or acetate ions, and the aforementioned non-halogen ionic groups are optionally further substituted with at least one halogen (such as F).

[0074] In some further examples, the polymerizable ionic liquid monomer has the structure of Formula III:

[0075] Formula III

[0076] R5 is selected from one of alkyl groups below C4 with terminal olefinic bonds, alkoxy groups, and optionally, the above groups are further substituted by one of halogen, oxygen, or C1-C2 alkyl groups.

[0077] R6 is selected from C3-C8 alkylene groups;

[0078] Q is selected from one of nitro, cyano, trifluoromethyl, quaternary ammonium, aldehyde, acyl, carboxyl, ester, amide, sulfonic acid, sulfonyl, and trialkyl halogroup;

[0079] Y +It is selected from one of the following: imidazole cationic groups, pyridine cationic groups, pyrrole cationic groups, and piperidine cationic groups;

[0080] Z - It is selected from one of halide ions, phosphate ions, perchlorate ions, sulfonamide ions, oxalate-borate ions, sulfonate ions, or acetate ions, and optionally, the above non-halogen ion groups are further substituted with at least one halogen.

[0081] In some examples, the crosslinking agent is selected from polyether-type poly(meth)acrylates containing at least two polymerizable (meth)acryloyloxy groups, whose molecular structure includes flexible polyoxyethylene segments (—(OCH2CH2)). m —, m≥1), and obtained by (meth)acrylate esterification of polyols or their ethoxylated derivatives as the backbone.

[0082] Exemplarily, the crosslinking agent includes, but is not limited to:

[0083] Di(meth)acrylates, such as triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, and polyethylene glycol diacrylate (PEGDA).

[0084] Tri(meth)acrylates, such as trimethylolpropane ethoxylate tri(meth)acrylate;

[0085] Tetra(meth)acrylates, such as pentaerythritol ethoxylate tetra(meth)acrylate.

[0086] The aforementioned crosslinking agent participates in polymerization via (meth)acryloyloxy to form a three-dimensional crosslinked network. In the system of this invention, di(meth)acrylate is preferred. The polyoxyethylene segments therein have both flexibility and lithium-ion solvation capability, which is beneficial to improving the mechanical strength and ionic conductivity of the solid electrolyte membrane.

[0087] The type of initiator in this invention is not particularly limited, as long as it can generate free radicals during the polymerization process and thus initiate monomer polymerization.

[0088] For example, the initiator may include, but is not limited to, one or more combinations of azo compounds, organic peroxide compounds, and inorganic peroxide compounds. Examples of azo compounds include azobisisobutyronitrile (AIBN) and azobisisoheptanenitrile (ABVN); examples of organic peroxide compounds include benzoyl peroxide (BPO) and lauroyl peroxide (LPO); and examples of inorganic peroxide compounds include potassium persulfate (KPS) and ammonium persulfate.

[0089] The diluent of the present invention is preferably a low polarity diluent. The diluent usually does not participate in the polymerization reaction and is mainly used to adjust the viscosity, wettability and ionic conductivity of the system, and to promote uniform wetting between the components of the system.

[0090] In some examples, the low-polarity diluent may include, but is not limited to, one or more combinations of fluoroalkanes, fluoroethers, hydrofluoroethers, and fluorocarbon compounds. Typical examples include, but are not limited to, 1,1,2,2-tetrafluoroethyl-2',2',2'-trifluoroethyl ether (TTE), bis(2,2,2-trifluoroethyl) ether (BTFE), ethyl 2,2,3,3-tetrafluoropropionate (TFEO), hydrofluoroether (HFE), methyl nonafluorobutyl ether, ethyl nonafluorobutyl ether, etc.

[0091] The alkali metal salt of the present invention is used to provide freely moving alkali metal ions in a polymer network to promote battery charging and discharging. The alkali metal salt also provides anions, which have good compatibility with the anions of polymerizable ionic liquid monomers and interact weakly with polymer chain molecules.

[0092] In some examples, the anion of the alkali metal salt comprises one or more of the following: halide ions, phosphate ions, perchlorate ions, sulfonamide ions, oxaloborate ions, sulfonate ions, or acetate ions, and the aforementioned non-halogen ion groups are optionally further substituted with at least one halogen (such as F); the cation of the alkali metal salt comprises one or more of the following: lithium ions, sodium ions, zinc ions, potassium ions, magnesium ions, or calcium ions.

[0093] As some more specific examples, the alkali metal salts include, but are not limited to, one or more of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxaloylborate) (LiBOB), and lithium difluorooxaloylborate (LiDFOB).

[0094] It should be added that, in the polymerizable ionic liquid monomer and alkali metal salt of the present invention, halide ions, as anions, typically have small radii, high charge densities, and are prone to forming strong hydrogen bonds, which usually leads to high reactivity and low adsorption and fixation strength of the system, easily weakening the interfacial stabilizing effect of compounds with phenylboronic acid pinacol ester groups on the halide solid electrolyte and polymerizable ionic liquid monomer. Therefore, the selection of anions is preferably organic anions, such as one or more of phosphate ions, perchlorate ions, sulfonylimide ions, oxaloborate ions, sulfonate ions, or acetate ions, and the above groups are optionally further substituted with at least one halogen (such as F); further preferred are anions with greater steric hindrance effects, such as one or more of sulfonylimide ions, oxaloborate ions, sulfonate ions, or acetate ions, and the above groups are optionally further substituted with at least one F.

[0095] The proportions of the components in this invention can be further optimized.

[0096] In some examples,

[0097] The mass ratio of the polymerizable ionic liquid monomer to the crosslinking agent is (8~12):1;

[0098] The additive is present in an amount of 5 wt% to 15 wt% of the total mass of the polymerizable ionic liquid monomer and crosslinking agent.

[0099] The initiator is present in an amount of 0.5 wt% to 1.5 wt% of the total mass of the polymerizable ionic liquid monomer and the crosslinking agent.

[0100] The mass ratio of the diluent to the total mass of the polymerizable ionic liquid monomer and the crosslinking agent is (1.5~2.5):1;

[0101] The molar concentration of the alkali metal salt relative to the total mass of the polymerizable ionic liquid monomer, crosslinking agent, and diluent is 0.75 mol / kg to 1.5 mol / kg.

[0102] The mass of the halide solid electrolyte is 20 wt% to 40 wt% of the total mass of the polymerizable ionic liquid monomer, crosslinking agent and diluent.

[0103] The preparation method of the composite solid electrolyte of the present invention is not limited, and it can be prepared by a common method.

[0104] As an example, the raw material components can be thoroughly mixed to form a prepolymer, which is then subjected to a polymerization reaction to obtain the final product. Understandably, polymerization reactions typically require pre-mixing or pre-assembling the prepolymer with other battery materials during battery assembly before initiating the polymerization reaction to transform it into a polymerized state.

[0105] The type of polymerization reaction is not particularly limited, as long as sufficient energy is provided to initiate the decomposition of the initiator or the activation of the monomer. The specific choice can be adapted based on the response characteristics (such as thermosensitivity or photosensitivity) of the selected initiator. For example, the polymerization reaction may include, but is not limited to, thermally initiated polymerization, photoinitiated polymerization, radiation-initiated polymerization, or microwave-initiated polymerization. Preferably, the polymerization reaction is thermally initiated polymerization, which aligns well with the temperature response characteristics of the exemplary initiator described above, resulting in good process compatibility.

[0106] The following detailed explanation will be provided with specific implementation examples.

[0107] Example 1

[0108] (1) Take 50g of 1-vinylimidazolium, 55g of 5-chloropentadienyl nitrile and 50g of ethyl acetate and add them to the reactor. Reflux and stir at 70℃ for 2h. After stirring, cool to room temperature, wash three times with 25g of ethyl acetate, and obtain the ionic liquid monomer by vacuum distillation.

[0109] (2) Take 50g of the ionic liquid monomer obtained in step (1) and 65g of LiTFSI and dissolve them in 100mL of deionized water. After stirring the reaction at room temperature for 2 hours, wash three times with 50mL of deionized water to obtain the ionic liquid monomer after ion exchange.

[0110] The reaction routes for steps (1) and (2) above are as follows:

[0111] .

[0112] (3) Under an inert atmosphere, take 2g of the ionic liquid monomer obtained in step (2), 0.2g of PEGDA (polyethylene glycol diacrylate, polymeric monomer), 0.011g of AIBN (azobisisobutyronitrile), 1.26g of LiTFSI (approximately 4.4 mmol), 0.11g of pinacol 4-acetoxyphenylboronic acid (a), and 2.2g of TTE. After stirring at room temperature for 2 hours, add 1.32g of Li with a D50 of 50 nm. 1.75 ZrCl 4.75 O 0.5 Stir for 1 hour and sonicate for 30 minutes to obtain the prepolymer of the composite solid electrolyte.

[0113] Example 2-11

[0114] The prepolymer of the composite solid electrolyte was prepared using the same method as in Example 1, except that the proportions of each component were varied in step (3). The specific proportions are listed in Table 1.

[0115] Example 12

[0116] The prepolymer of the composite solid electrolyte was prepared using the same method as in Example 8, except that in step (1), the raw material 1-vinylimidazolium was replaced with 4-vinylpyridine. The reaction routes for steps (1) and (2) are as follows:

[0117] .

[0118] Example 13

[0119] The prepolymer of the composite solid electrolyte was prepared using the same method as in Example 12, except that 4-acetoxyphenylboronic acid pinacol ester (a) was replaced with 4-fluorobenzylboronic acid pinacol ester (f).

[0120] Example 14

[0121] The prepolymer of the composite solid electrolyte was prepared using the same method as in Example 12, except that 4-acetoxyphenylboronic acid pinacol ester (a) was replaced with 4-(cyanomethyl)phenylboronic acid pinacol ester (g).

[0122] Comparative Example 1

[0123] Under an inert atmosphere, take 2g of ethyl cyanoacrylate ( (CAS: 106-71-8), 0.2g PEGDA, 0.022g AIBN, 1.89g LiTFSI (approx. 6.6mmol), 0.22g 4-(cyanomethyl)phenylboronic acid pinacol ester, 4.4g TTE, stirred at room temperature for 2h, then approximately 1.98g Li with D50 of 50nm was added. 1.75 ZrCl 4.75 O 0.5 Stir for 1 hour and sonicate for 30 minutes to obtain composite solid electrolyte prepolymer.

[0124] Comparative Example 2

[0125] The prepolymer of the composite solid electrolyte was prepared using the same method as in Example 14, except that in step (3), 4-(cyanomethyl)phenylboronic acid pinacol ester (g) was replaced with methylboronic acid pinacol ester (m).

[0126]

[0127] m

[0128] Comparative Example 3

[0129] The prepolymer of the composite solid electrolyte was prepared using the same method as in Example 14, except that in step (3), 4-(cyanomethyl)phenylboronic acid pinacol ester (g) was replaced with p-methylphenylacetonitrile (n).

[0130]

[0131] n

[0132] Comparative Example 4

[0133] The prepolymer of the composite solid electrolyte was prepared using the same method as in Example 14, except that 4-(cyanomethyl)phenylboronic acid pinacol ester (g) was not added in step (3).

[0134] Table 1

[0135]

[0136] The prepolymers of the above embodiments and comparative examples were used to assemble batteries and undergo polymerization reactions to obtain composite solid electrolytes in situ in the batteries, and their performance was tested.

[0137] Room temperature ionic conductivity test: A composite solid electrolyte was used as the electrolyte material, and a 270µm thick glass fiber membrane was used as the separator. SS-SS coin cells were assembled and heated at 80℃ for 1 hour, and their EIS was tested in an electrochemical test. The ionic conductivity was calculated using the formula σ=L / (RS), where L is the thickness of the solid electrolyte, R is the impedance of the mold cell, and S is the cross-sectional area of ​​the solid electrolyte.

[0138] Lithium-ion transference number test: A composite solid electrolyte prepolymer was used as the electrolyte material and a 25µm thick PP film was used as the separator. A Li-Li battery was assembled and heated at 80℃ for 1 hour. The test was performed by electrochemical cycle testing. The test steps were EIS-CA-EIS.

[0139] Through formula Calculate the lithium-ion transference number, where R0 and R... s These are the interfacial impedances between the electrode and the electrolyte before and after polarization, respectively, where I0 and I0 are... s These represent the current of the coin cell before and after polarization, respectively, with ΔV set to 10mV.

[0140] For partial lithium-ion transference number test plots, please refer to Figure 1-6 As shown.

[0141] Electrical performance testing: A composite solid electrolyte prepolymer was used as the electrolyte material, and a 25µm thick PP film was used as the separator. An NCM (NCM:Super P:PVDF=8:1:1)-Li battery was assembled. After heating at 80℃ for 1 hour, it was charged and discharged at a rate of 1C in the voltage range of 2.8-4.2V at room temperature.

[0142] The test results are listed in Table 2.

[0143] Table 2

[0144]

[0145] The experimental results of the various embodiments and comparative examples of the present invention fully demonstrate the advantages of the compound system of the present invention in ensuring the processability of electrolyte film formation, balancing and improving the full contact of the organic-inorganic interface, and maintaining the stability of the interface during long-cycle charging at fast charging rates.

[0146] In Comparative Example 1, the polymerizable ionic liquid monomer was replaced with the general polymer monomer ethyl cyanoacrylate. Although the polymer monomer still retained functional groups such as cyano groups, the non-molten salt monomer did not have the high polarity and high flexibility of anions and cations, and its contact ability with dispersed particles (halide solid electrolyte) was limited. It was difficult to overcome the system compatibility problem and good basic interface, and its ion conduction and cycling ability were poor.

[0147] Comparative Example 4 did not use additives to optimize and control the interface between the halide solid electrolyte and the polymerizable ionic liquid monomer. Even after the two were combined, there was basically no significant improvement in the various performance indicators.

[0148] Although the methylboronic acid pinacol ester used in Comparative Example 2 employed a sterically hindered additive with a dioxoboron five-membered ring, the lack of benzene ring electron cloud in the additive structure to regulate the orbital of B, and the failure to form π-π stacking of the additive with the ring structure in the ionic liquid monomer through the benzene ring, made B susceptible to metathesis by the active metal element M in the halide solid electrolyte. At the same time, the weakened adsorption effect of the additive exacerbated this interfacial instability. Therefore, although the ionic conductivity of the composite electrolyte was slightly improved compared to Comparative Example 4, the long-cycle capacity retention rate was actually reduced.

[0149] The additive p-methylphenylacetonitrile used in Comparative Example 3 only introduced benzene ring conjugation, which promoted the mutual adsorption and fixation of the additive on the ionic liquid, but lacked the fixation and adsorption of B anions in the high salt system. Significant concentration polarization still existed in the high salt system, and the performance effect was not ideally improved.

[0150] Examples 1-11 use a fixed additive, 4-acetoxyphenylboronic acid pinacol ester, as an example to explore the influence of the distribution ratio of each component in the system.

[0151] Examples 1-3 illustrate the effect of the initiator. As the amount of initiator gradually increases, the ionic conductivity initially increases and then decreases. When the amount of initiator added is small, the polymer molecular weight is large. The large molecular weight makes chain segment peristalsis difficult, reducing lithium-ion transport. When the molecular weight is too high, although the molecular weight decreases, the degree of monomer polymerization in the system is relatively large, and the small molecule polymer has a limited effect on promoting molecular chain peristalsis, so the ionic conductivity is also not high.

[0152] Examples 2, 4, and 5 reflect the different amounts of diluent used. Appropriate diluent addition is beneficial to the compatibility of the system and thus improves the ionic conductivity. However, after polymerization in Example 5, the composite solid electrolyte began to show a semi-solid state. Too much diluent can also affect the degree of polymerization crosslinking, or cause more residual leakage after the diluent has polymerized. This makes it impossible to maintain solid characteristics and meet the application requirements of all-solid-state batteries. It is also not conducive to the construction of a three-dimensional transport network structure. The lithium-ion transference number and battery cycle performance are both reduced.

[0153] Examples 4, 6, and 7 reflect the concentration changes of different alkali metal salts. In Example 6, the alkali metal salt concentration was low, and the concentration of lithium ions generated during dissociation was also low, which affected the lithium ion transport efficiency. In Example 7, the alkali metal salt concentration was high, and the excess alkali metal could not be completely dissociated, or it provided too many anions in the system, which was not conducive to the optimization of ionic conductivity.

[0154] Examples 4, 8, and 9 illustrate the effects of different additive amounts. As crucial interfacial control media between the halide solid electrolyte and the polymerizable ionic liquid monomer in this invention, the appropriate dosage of additives significantly impacts electrical performance. With increasing additive dosage, the lithium-ion transference number initially increases and then stabilizes, a result of the coordinated effects of multiple adsorption and conjugation. When the additive dosage is low, the number of adsorbed anions is also small, limiting only some anion migration. When the additive dosage is excessive, exceeding the number of additive molecules that can be conjugated and adsorbed by the heterocyclic cation groups in the polyionic liquid, the increase in lithium-ion transference number is smaller. Excessive addition affects lithium-ion transport in the electrolyte, reduces ionic conductivity, and impacts the cycle stability of the prepared battery.

[0155] Examples 8, 10, and 11 further illustrate the effects of different amounts of halide solid electrolyte added. As a crucial component of the system, the amount of halide electrolyte is inevitably related to the amount of polymerizable ionic liquid monomers and additives. Halide solid electrolytes have a complex effect, lowering the glass transition temperature of polymers, increasing the free volume of polymers, improving the mobility of polymer chains, and providing skeletal support in flexible systems, thereby enhancing lithium-ion transport capabilities. When the amount added is too small, the improvement effect is poor; for example, the ionic conductivity of the electrolyte in Example 10 tends to decrease. When the amount added is too large, dispersion and interface issues are exacerbated, system mismatch affects lithium-ion transport, and also reduces the ionic conductivity of the electrolyte, impacting the cycle stability of the battery.

[0156] The above results indicate that the components in the system need to be coordinated with each other within a suitable ratio range.

[0157] Examples 8 and 12 demonstrate the effect of different heterocyclic cationic groups in polymerizable ionic liquid monomers. The pyridine group in Example 12 is a six-membered ring, which has a structure more similar to the benzene ring and a stronger π-π stacking ability, which is beneficial for enhancing the ability to confine anion migration and increasing the lithium ion transference number.

[0158] Examples 13 and 14 further demonstrate the influence of different substituents on the benzene ring in the additive on its interface regulation ability. Comparing Examples 12 and 14, it can be seen that Example 14 uses a substituent with strong electron-withdrawing ability, which, compared to the weak electron-donating acetoxy group in Example 12, significantly improves the lithium-ion transference number and battery cycle stability of the composite solid electrolyte in the system of this invention. Meanwhile, compared to Example 13, although the substituent of F is also an electron-withdrawing group and shows the same trend of improving lithium-ion transference number and battery cycle stability, on the other hand, because the benzene ring and dioxoboron ring in the compound structure of the additive are not directly connected (n=1), the dual effect of the benzene ring in feeding electrons to B and reducing acidity, as well as protecting B from dissociation, is reduced. Macroscopically, this results in a trend of decreasing rather than increasing ionic conductivity in the composite solid electrolyte, and the overall improvement in lithium-ion transference number and battery cycle stability is relatively limited.

[0159] The technical features of the embodiments described above can be combined arbitrarily. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as the combination of these technical features does not contradict each other, it should be considered within the scope of this specification. Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make modifications, alterations, substitutions, and variations to the above embodiments within the scope of the present invention. Furthermore, without contradiction, those skilled in the art can combine and integrate different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

Claims

1. A composite solid electrolyte, the raw materials of which include polymerizable ionic liquid monomers, crosslinking agents, additives, initiators, diluents, alkali metal salts and halide solid electrolytes; The additive is selected from at least one of compounds having a phenylboronic acid pinacol ester group.

2. The composite solid electrolyte according to claim 1, characterized in that: The mass ratio of the polymerizable ionic liquid monomer to the crosslinking agent is (5~20):1; The additive is present in an amount of 5 wt% to 20 wt% of the total mass of the polymerizable ionic liquid monomer and crosslinking agent. The initiator is present in an amount of 0.5 wt% to 5 wt% of the total mass of the polymerizable ionic liquid monomer and the crosslinking agent. The mass ratio of the diluent to the total mass of the polymerizable ionic liquid monomer and the crosslinking agent is (1~5):1; The molar concentration of the alkali metal salt relative to the total mass of the polymerizable ionic liquid monomer, crosslinking agent, and diluent is 0.5 mol / kg to 2 mol / kg. The mass of the halide solid electrolyte is 10 wt% to 50 wt% of the total mass of the polymerizable ionic liquid monomer, crosslinking agent, and diluent. Preferred, The mass ratio of the polymerizable ionic liquid monomer to the crosslinking agent is (8~12):1; The additive is present in an amount of 5 wt% to 15 wt% of the total mass of the polymerizable ionic liquid monomer and crosslinking agent. The initiator is present in an amount of 0.5 wt% to 1.5 wt% of the total mass of the polymerizable ionic liquid monomer and the crosslinking agent. The mass ratio of the diluent to the total mass of the polymerizable ionic liquid monomer and the crosslinking agent is (1.5~2.5):1; The molar concentration of the alkali metal salt relative to the total mass of the polymerizable ionic liquid monomer, crosslinking agent, and diluent is 0.75 mol / kg to 1.5 mol / kg. The mass of the halide solid electrolyte is 20 wt% to 40 wt% of the total mass of the polymerizable ionic liquid monomer, crosslinking agent and diluent.

3. The composite solid electrolyte according to claim 1, characterized in that: The halide solid electrolyte has the general formula Li a M b X c Y d Where 1.5≤a≤3, 0.5≤b≤1.5, 3.5≤c≤6.5, 0≤d≤1.0; M is selected from at least one of Zr, Hf, Ti, Ta, Nb, Y, Sc, In, Al, Mg, Zn, and La; X is selected from at least one of Cl, Br, and I; Y is selected from at least one of O, S, and Se; and when d>0, the electrolyte is an oxyhalide solid electrolyte, a sulfide solid electrolyte, or a selenium halide solid electrolyte. The structure of compound I having a phenylboronic acid pinacol ester group: Equation I, Where n = 0 or 1, n = 0 indicates that C and B on the benzene ring are directly connected; R1, R2, and R3 are each independently selected from H, halogen, ether, hydroxyl, carboxyl, carbonyl, amino, cyano, isocyano, nitro, nitroso, acyloxy, amide, azide, formyl, carbamoyl, silyl, siloxy, mercapto, sulfonic acid, sulfonyl, sulfinyl, ester, C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, borate, phosphate, C3-C4 cycloalkyl, ternary or quaternary heterocyclic groups, and optionally further substituted by hydrogen, halogen, hydroxyl, cyano, amino, C1-C4 alkyl or C1-C4 alkoxy.

4. The composite solid electrolyte according to claim 1, characterized in that: The halide solid electrolyte is an oxyhalide solid electrolyte; The polymerizable ionic liquid monomer is an ionic liquid monomer containing a heterocyclic cation center; The structure of compound I having a phenylboronic acid pinacol ester group: Equation I, Where n=0; R1, R2, and R3 are each independently selected from H, halogen, ether, hydroxyl, carboxyl, carbonyl, amino, cyano, isocyano, nitro, nitroso, acyloxy, amide, azide, formyl, carbamoyl, silyl, siloxy, mercapto, sulfonic acid, sulfonyl, sulfinyl, ester, C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, borate, phosphate, C3-C4 cycloalkyl, ternary or quaternary heterocyclic groups, and optionally further substituted by hydrogen, halogen, hydroxyl, cyano, amino, C1-C4 alkyl or C1-C4 alkoxy.

5. The composite solid electrolyte according to claim 1, characterized in that: The halide solid electrolyte is selected with a nanoscale particle size, preferably with a D50 of 5~300nm, and more preferably with a D50 of 5~100nm.

6. The composite solid electrolyte according to claim 1, characterized in that: The oxyhalide solid electrolyte uses M containing at least Zr, and d satisfies 0.1≤d≤1.0; Preferably, the oxyhalide solid electrolyte has the general formula Li a Zr b-α M' α Cl c O d , where 1.5≤a≤2, 0.9≤b≤1.1, 0≤α≤0.3, 3.5≤c≤5.5, 0.1≤d≤1.0; M' is selected from at least one of Hf, Ti, Ta, Nb, Y, Sc, In, Al, Mg, Zn, and La.

7. The composite solid electrolyte according to claim 1, characterized in that: In the compound having a pinacol ester group of phenylboronic acid, an electron-withdrawing functional group is attached to the benzene ring; or, in the compound having a pinacol ester group of phenylboronic acid, the benzene ring is an electron-withdrawing modified benzene ring. Preferably, the structure of compound II having a phenylboronic acid pinacol ester group is as follows: Formula II R4 is selected from an electron-withdrawing functional group whose main chain length does not exceed four atoms; preferably a strongly electron-withdrawing functional group; specifically, it can be selected from one of nitro, cyano, trifluoromethyl, quaternary ammonium, aldehyde, acyl, carboxyl, ester, amide, sulfonic acid, sulfonyl and trialkyl halogroup. Preferably, the compound having a phenylboronic acid pinacol group is selected from at least one of 4-acetoxyphenylboronic acid pinacol ester, 3-cyano-4-fluorophenylboronic acid pinacol ester, 4-trimethylsilylphenylboronic acid pinacol ester, phenylboronic acid pinacol ester, 3,5-bis(methoxycarbonyl)phenylboronic acid pinacol ester, 4-fluorobenzylboronic acid pinacol ester, 4-(cyanomethyl)phenylboronic acid pinacol ester, 2-(azidomethyl)phenylboronic acid pinacol ester; 4-methoxycarbonylphenylboronic acid pinacol ester; 2-fluoro-5-(methoxycarbonyl)phenylboronic acid pinacol ester; and 3-chloro-4-nitrophenylboronic acid pinacol ester.

8. The composite solid electrolyte according to claim 1, characterized in that: The polymerizable ionic liquid monomer includes at least one of those having a nitrogen heterocyclic cation center group; Preferably, the central nitrogen heterocyclic cation group is selected from one of imidazole cationic groups, pyridine cationic groups, pyrrole cationic groups, and piperidine cationic groups; Preferably, the polymerizable group of the polymerizable ionic liquid monomer is selected from at least one of vinyl, propenyl, allyl, and acryloyloxy groups; Preferably, the anionic group of the polymerizable ionic liquid monomer is selected from one of halide ions, phosphate ions, perchlorate ions, sulfonylimide ions, oxalate-borate ions, sulfonate ions or acetate ions, and the above-mentioned non-halogen ion groups are optionally further replaced by at least one halogen. Preferably, the polymerizable ionic liquid monomer has the structure of Formula III: Formula III R5 is selected from one of alkyl groups below C4 with terminal olefinic bonds, alkoxy groups, and optionally, the above groups are further substituted by one of halogen, oxygen, or C1-C2 alkyl groups. R6 is selected from C3-C8 alkylene groups; Q is selected from one of nitro, cyano, trifluoromethyl, quaternary ammonium, aldehyde, acyl, carboxyl, ester, amide, sulfonic acid, sulfonyl, and trialkyl halogroup; Y + It is selected from one of the following: imidazole cationic groups, pyridine cationic groups, pyrrole cationic groups, and piperidine cationic groups; Z - It is selected from one of halide ions, phosphate ions, perchlorate ions, sulfonamide ions, oxalate-borate ions, sulfonate ions, or acetate ions, and optionally, the above non-halogen ion groups are further substituted with at least one halogen.

9. The composite solid electrolyte according to claim 1, characterized in that: The crosslinking agent is selected from polyether-type poly(meth)acrylates containing at least two polymerizable (meth)acryloyloxy groups; Preferably, the crosslinking agent comprises: Di(meth)acrylates, specifically including at least one of triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, and polyethylene glycol diacrylate; Tri(meth)acrylates, specifically including trimethylolpropane ethoxylates; Tetra(meth)acrylates, specifically including pentaerythritol ethoxylate tetra(meth)acrylate; Preferred, The initiator includes A combination of one or more of the following: azo compounds, organic peroxides, and inorganic peroxides; The azo compounds include at least one of azobisisobutyronitrile and azobisisoheptanenitrile; The organic peroxide compounds include at least one of benzoyl peroxide and lauroyl peroxide; The inorganic peroxide compounds include at least one of potassium persulfate and ammonium persulfate; Preferred, The diluent is selected from at least one of the low-polarity diluents; More preferably, the low-polarity diluent specifically includes one or more combinations of fluoroalkanes, fluoroethers, hydrofluoroethers, and fluorocarbonate compounds; More preferably, the low polarity diluent specifically includes at least one of 1,1,2,2-tetrafluoroethyl-2',2',2'-trifluoroethyl ether, bis(2,2,2-trifluoroethyl) ether, ethyl 2,2,3,3-tetrafluoropropionate, hydrofluoroether, methyl nonafluorobutyl ether, and ethyl nonafluorobutyl ether. Preferred, The anion of the alkali metal salt includes one or more of the following: halide ions, phosphate ions, perchlorate ions, sulfonamide ions, oxalate-borate ions, sulfonate ions, or acetate ions, and the above non-halogen ion groups are optionally further substituted by at least one halogen. The cation of the alkali metal salt includes one or more of lithium ions, sodium ions, zinc ions, potassium ions, magnesium ions, or calcium ions. Preferably, the alkali metal salt includes one or more of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxaloacetate borate, and lithium difluorooxaloacetate borate. Preferably, the anion in the polymerizable ionic liquid monomer and / or alkali metal salt is selected from at least one organic anion.

10. A solid-state battery comprising the composite solid-state electrolyte according to any one of claims 1-9.